Co-shopper and price moderation in the influence of tourist ethnocentrism and brand images on purchase intention - Suryaningsih, Ika Barokah (BISMA (Bisnis dan Manajemen), 2020)
Purchase intention provides a motivational effect that always recorded in the consumer mind and influential to their consumption behavior. The purpose of this study was to examine the role of co-shopper and price as moderating variables in the relationship between tourist ethnocentrism and brand image on purchase intention. The population in this study were local tourists who visited Banyuwangi and Osing t-shirt stores. The sampling technique was an accidental sampling that collected data from 100 respondents. The analytical method was Moderated Regression Analysis (MRA). The results showed that tourist ethnocentrism and brand image have a positive effect on purchase intention. The influence of tourist ethnocentrism and brand image on purchase intention is stronger when it moderated by the co-shopper variable. Conversely, the influence of tourist ethnocentrism and brand image on purchase intention was statistically not significantly moderated by price.